Research Status and Direction of Chronic Obstructive Pulmonary Disease Complicated with Coronary Heart Disease: A Bibliometric Analysis from 2005 to 2024 - Bian H; Zhu S; Xing W; Qi L; Xue J; Peng X; Jin Z; Zhao H (International Journal of COPD)
Hupo Bian,1,* Shaoqi Zhu,2,* Wenjian Xing,3 Luying Qi,1 Jingnan Xue,1 Xiuhua Peng,1 Zanhui Jin,1 Hongxing Zhao1,4 1Department of Radiology, The First Affiliated Hospital of Huzhou University, Huzhou, Zhejiang, People’s Republic of China; 2Department of Endocrinology, The First Affiliated Hospital of Huzhou University, Huzhou, Zhejiang, People’s Republic of China; 3Department of Radiology, The Linghu People’s Hospital, Huzhou, Zhejiang, People’s Republic of China; 4Huzhou Key Laboratory of Precise Diagnosis and Treatment of Urinary Tumors, Huzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongxing Zhao, Department of Radiology, Huzhou First People’s Hospital, The First Affiliated Hospital of Huzhou University, No. 158, Plaza Back Road, Wuxing District, Huzhou City, Zhejiang Province, People’s Republic of China, Email 50073@zjhu.edu.cnObjective: There is increasing evidence that chronic obstructive pulmonary disease (COPD) is associated with coronary heart disease (CHD). In this study, we provide valuable insights in the field by examining the evolution of the relationship between COPD and CHD over the past 20 years.Methods: A comprehensive computer search was conducted in the Web of Science (WOS) core dataset, covering literature on COPD combined with CHD from January 1, 2005, to August 20, 2024. Visual analyses were performed using VOSviewer, CiteSpace, and Bibliometrix to assess countries, institutions, the centrality of institutional intermediaries, authorship patterns, including co-cited authors and references, and keywords; Excel (version 2021) software was utilized for generating relevant descriptive analysis tables.Results: A total of 2420 publications sourced from WOS were included in this study. Since 2005, there has been a continuous increase in the literature about COPD combined with CHD; polynomial fitting yielded an R² value of 0.7758. The volume of literature in this domain is projected to continue growing steadily. The United States emerged as the leading country by publication count; Lin Cheng-li ranked first among authors, while China Medical University topped institutional contributions. Notably, Sin dd, Mannino dm, and Helvaci Mr were identified as the top three authors based on citation frequency. The Journal of Vascular Surgery recorded the highest number of publications, whereas The Lancet was recognized as the most influential among the top ten co-cited journals. The most frequently cited reference pertains to systemic inflammation’s role in increasing cardiovascular risk among patients with COPD. Through keyword clustering analysis, we categorized all keywords into three distinct groups: management strategies for COPD and CHD; diseases associated with both conditions; and epidemiological characteristics concerning their burden—current hotspots include multimorbidity factors such as hypertension and obesity alongside outcomes like diagnosis during COVID-19 pandemic implications within societal contexts are highlighted here too.Conclusion: Presently focused research on COPD coupled with CHD primarily revolves around five key areas: pathogenesis exploration, early diagnostic techniques, COVID-19 infection, dynamics intervention, methodologies, and treatment protocol development efforts. To improve the early detection rate of COPD complicated with CHD, the main development direction in the future is to extract computed tomography (CT) features using imaging omics and establish an early prediction model. The results of this study will provide new ideas and directions for subsequent related research.Keywords: chronic obstructive pulmonary disease, COPD, coronary heart disease, CHD, inflammation, bibliometrics, visual analysis